From products to publics? The potential of participatory design for research on youth, safety and well-being. (15th March 2016) - Collin, Philippa; Swist, Teresa
ABSTRACT: This paper considers how 'participation' features as a key concept in contemporary approaches to research, policy and interventions to promote young people's experiences of safety and well-being in digital society. In particular, it examines the potential of participatory design (PD) methodology as a way of expressing, surfacing and supporting engagement with youth perspectives in research and design projects. In doing so, we explore how the language, materials and processes of a PD approach can help reconfigure the aims of research beyond the production of 'products' towards fostering 'youth-inclusive publics'. Drawing on the concept of 'infrastucturing' and 'attachments' [Le Dantec, C. A., and C. DiSalvo. 2013. "Infrastructuring and the Formation of Publics in Participatory Design." Social Studies of Science 43 (2): 241–264. doi:10.1177/0306312712471581 ], the paper reflects on an Australian research project to develop online campaigns to promote youth safety and well-being in digital society. From our analysis emerged three commitments of PD with young people that help articulate, make visible and unpack 'attachments' to concepts of youth, technology and well-being and provide new opportunities for engagement with youth experience in research and intervention design. We find that these commitments – the embodiment of context; the enactment of creativity and the emergence of connectivity – offer novel insights on youth participation in complex research projects. Moreover, foregrounding these commitments through PD can build shared vocabularies, artefacts and processes of engagement with young people in research projects focused on youth safety and well-being.